PERAN KAIDAH FIQHIYAH “ الضرر يُزال “ PADA KASUS KEKERASAN DALAM RUMAH TANGGA - Hanina Maria Ulfa; M. Nabat Ardli (Makkah: Journal Of Islamic Studies, 2025)
: This study aims to analyze the role of the fiqh legal maxim “الضرر يُزال” (harm must be eliminated) in responding to and addressing cases of domestic violence. This maxim is one of the kulliyyah (universal) principles in Islamic jurisprudence that holds a strategic position in resolving social issues, particularly those concerning the protection of individuals from harm and injustice. The research employs a library research approach by reviewing classical and contemporary literature related to fiqh legal maxims, Islamic family law, and studies on domestic violence from both legal and social perspectives. The findings indicate that domestic violence—whether physical, psychological, verbal, or economic—constitutes a form of ḍarar (harm) that must be eliminated according to Islamic legal principles. The maxim “الضرر يُزال” provides a normative foundation for intervention in domestic settings, whether by individuals, religious institutions, or the state, to protect victims and prevent further violence. Moreover, this maxim aligns with the objectives of Islamic law (maqāṣid al-syarī‘ah), particularly the preservation of life (ḥifẓ al-nafs) and dignity (ḥifẓ al-‘irḍ). This research recommends the reconstruction of Islamic family jurisprudence to be more empathetic, just, and responsive to social realities. Additionally, there is a need for synergy between Islamic legal thought, state law, and social movements to ensure that the principle of harm elimination is effectively applied in Muslim family life. Thus, the maxim “الضرر يُزال” should not only remain a theoretical concept but also function as an ethical and practical principle to foster harmonious, safe, and just families.